2014
DOI: 10.1371/journal.pone.0090141
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin Protein Level, a Potential Predictive Marker for Taxane Treatment Response in Endometrial Cancer

Abstract: Stathmin is a prognostic marker in many cancers, including endometrial cancer. Preclinical studies, predominantly in breast cancer, have suggested that stathmin may additionally be a predictive marker for response to paclitaxel. We first evaluated the response to paclitaxel in endometrial cancer cell lines before and after stathmin knock-down. Subsequently we investigated the clinical response to paclitaxel containing chemotherapy in metastatic endometrial cancer in relation to stathmin protein level in tumors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 49 publications
(62 reference statements)
2
23
0
1
Order By: Relevance
“…FFPE tumor tissue sections from GOG-177 were evaluated for expression of stathmin (#3352, Cell Signaling, Danvers, MA), via IHC per the manufacturer's recommendations and as shown by other investigators [5,13]. A western blot analysis using 8 different cell lines and IHC utilizing positive and negative control slides were performed to confirm specificity of the antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FFPE tumor tissue sections from GOG-177 were evaluated for expression of stathmin (#3352, Cell Signaling, Danvers, MA), via IHC per the manufacturer's recommendations and as shown by other investigators [5,13]. A western blot analysis using 8 different cell lines and IHC utilizing positive and negative control slides were performed to confirm specificity of the antibody.…”
Section: Methodsmentioning
confidence: 99%
“…Stathmin expression has been widely analyzed in endometrial tumors and is known to be part of the machinery required for rapid cell transit through mitosis [4]. In addition, stathmin expression has been shown to negatively correlate with response to chemotherapeutic regimens that contain paclitaxel, an association that has been observed in multiple cancer types [5-11]. As paclitaxel is a microtubule stabilizing agent that prevents successful completion of mitosis [12], i.e., a potential molecular antagonist to stathmin, we hypothesized that it could counteract the impact of high stathmin expression in high risk cases.…”
Section: Introductionmentioning
confidence: 99%
“…Stathmin is frequently overexpressed in many human cancers including lung (Han et al, 2013), bladder (Wosnitzer et al, 2011), endometrial (Werner et al, 2014), and oral cancer (Kouzu et al, 2006) and Yuan et al reported that the high level of stathmin expression is required for the maintenance of high proliferation rate of tumor cells (Yuan et al, 2012), however information of stathmin expression in esophageal carcinoma is limited thus far. In order to clarify the relative status of stathmin in EC, we detected the mRNA and protein expression of stathmin in human esophageal carcinoma tissues using immunocytochemistry, and in situ hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…Stathmin is a cytosolic phosphoprotein and regulator of the microtubule cytoskeleton and cell cycle [11] and is also a highly relevant biomarker in EC [12] , with overexpression demonstrated in between 27 and 57% [12] . It has prognostic significance in several malignancies, including EC [13][14][15][16][17][18][19][20][21][22] , and there is evidence for its prognostic and predictive value for metastases [12,21] and response to taxane chemotherapy [20,[23][24][25] . There is also evidence for stathmin as a surrogate marker of phosphoinositide 3-kinase (PI3K) pathway activation [19] , one of the most commonly aberrant pathways in EC, and is associated with phosphatase and tensin homologue (PTEN) loss and phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) amplification [19,26] .…”
Section: Introductionmentioning
confidence: 99%